PEMBERIAN REWARD UNTUK MENINGKATKAN SEMANGAT BELAJAR SISWA KELAS III DI MIN 1 TANJUNG AGUNG KOTA BENGKULU - Rahma, Khodijah; Vistika Natasyah; Izzah Ulfa; Mely Aldariani; Jessy Mittria (JURNAL ILMU PENDIDIKAN, 2025)
The author chose to conduct research entitled The Effect of Appreciation for Giving Money on Students' Enthusiasm for Learning at MIN 1 Tanjung Agung, Bengkulu City with the aim of finding out the enthusiasm for learning of grade III students, and the things that influence students to be active and enthusiastic in studying, especially in the subject of History of Islamic Culture. With this research, the author examines the learning process which includes methods, media and approaches used by teachers so as to increase students' enthusiasm for learning in SKI learning in the classroom. This research method uses a quantitative approach with field research, involving SKI teachers and grade III students. From this research the author found that in the SKI learning process, one of the SKI Subject Teachers at MIN 1 Tanjung Agung, Bengkulu City used a giving system. money to students as appreciation for student activity. The results of the research show that giving money by SKI subject teachers can increase students' enthusiasm for learning in class III.